Draw attention to the teratogenic effect of DMD in MS treatment - Shi-Fang Hou; Yin Jian; Li-Yan Qiao; Zun-Bao Li; Kai Feng; Xian-Hao Xu (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2020)
More than 2.3 million people are affected by Multiple Sclerosis (MS) worldwide. Since the 1990s, disease modifying drug (DMD) has been developing increasingly. With more and more clinical applications, more and more attention has been paid to the adverse effects of DMD in the treatment of MS. DMD selection for patients with MS during pregnancy is one of the most important topics for neuroimmunologists and obstetrics. This comment is mainly based on our published and forthcoming data.